2008
DOI: 10.1124/dmd.108.022640
|View full text |Cite
|
Sign up to set email alerts
|

Application of Molecular Modeling for Prediction of Substrate Specificity in Cytochrome P450 1A2 Mutants

Abstract: ABSTRACT:Molecular dynamics (MD) simulations of 7-ethoxy-and 7-methoxyresorufin bound in the active site of cytochrome P450 (P450) 1A2 wild-type and various mutants were used to predict changes in substrate specificity of the mutants. A total of 26 multiple mutants representing all possible combinations of five key amino acid residues, which are different between P450 1A1 and 1A2, were examined. The resorufin substrates were docked in the active site of each enzyme in the productive binding orientation, and MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 32 publications
4
29
1
2
Order By: Relevance
“…The overall yield of purified enzyme was approximately 20 to 40%, similar to that reported previously (Liu et al, 2004;Tu et al, 2008;Huang and Szklarz, 2010). The purity of CYP1A1 and CYP1A2 verified by SDS-polyacrylamide gel electrophoresis and Western blots indicated that the proteins were at least 95% pure.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The overall yield of purified enzyme was approximately 20 to 40%, similar to that reported previously (Liu et al, 2004;Tu et al, 2008;Huang and Szklarz, 2010). The purity of CYP1A1 and CYP1A2 verified by SDS-polyacrylamide gel electrophoresis and Western blots indicated that the proteins were at least 95% pure.…”
Section: Resultssupporting
confidence: 63%
“…The differences in activities probably arise from structural differences between CYP1A1 and CYP1A2. Our previous studies indicated that five key residues in the active site that differ between the enzymes play a role in the determination of substrate specificity with alkoxyresorufins (Liu et al, 2003(Liu et al, , 2004Tu et al, 2008) and phenacetin (Huang and Szklarz, 2010). In CYP1A1, the unique active site residues are Ser122, Asn221, Gly225, Leu312, and Val382, which correspond to Thr124, Thr223, Val227, Asn312, and Leu382 of CYP1A2, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting trajectory was analyzed to find the best substrate orientation, and the enzymesubstrate complex was minimized for another 1000 steps, as described earlier. This optimal substrate orientation was used as a starting point for automated docking with the Affinity module of Insight II using default parameters, as described earlier (Ericksen and Szklarz, 2005;Tu et al, 2008;Huang and Szklarz, 2010;Walsh et al, 2013). Residues within 10 Å from the initial substrate position comprised the flexible region of the protein during all docking runs.…”
Section: Structural Computational and Functional Analysis Of Cyp2b3mentioning
confidence: 99%
“…Moreover, mutations at position 382 in both CYP1A1 and CYP1A2 shifted substrate specificity from one enzyme to another (Liu et al, 2004). Further computational and experimental studies with multiple CYP1A2 mutants confirmed the importance of this residue for alkoxyresorufin oxidation (Tu et al, 2008). Therefore, it would be of interest to examine the effect of these mutations on oxidation of other types of substrates.…”
mentioning
confidence: 99%